The Impact of the Information and Communication Technology and Electricity on Inter-island Interactions in Indonesia - Rosmika, Nuri; Masbar, Raja; Syahnur, Sofyan; Suriani, Suriani (International Journal of Energy Economics and Policy, 2022)
The purpose of this study is to examine the economic interaction in Indonesia and the impact of the Information and Communication Technology (ICT) and electricity on inter-island interactions in Indonesia. Data used Indonesian Inter-Regional Input-Output (IRIO) table 2016. The result is the largest inter-island interaction occurred between Java and Sumatra, Java-Sulawesi and Java-Kalimantan. Java was more dependent on Sumatra than Sumatra's dependence on Java. Java was more dependent on other islands than other islands' dependence on Java. The impact of ICT on the economy was higher than the impact of electricity. The ICT had more impact on the interregional economy than intraregional. Meanwhile, the electricity had more effect on the intraregional economy than interregional. The intervention to increase investment in ICT resulted in the highest increase in output of Bali and Nusa Tenggara. Both when the intervention was carried out on Bali and Nusa Tenggara islands or in other islands. The same was true for electricity investment interventions. Therefore, Bali and Nusa Tenggara islands should be given more priority in ICT and electricity investment. Investment in ICT and electricity will accelerate the economic development of eastern Indonesia so that it can become a reference for equitable development.